PENGARUH EKSTRAKURIKULER PENCAK SILAT TAPAK SUCI TERHADAP PENINGKATAN KARAKTER DISIPLIN SISWA DI SD MUHAMMADIYAH SUGIO LAMONGAN - Afifuddin, Muhammad; Nurdiana, Ratna; Machsunah, Yayuk Chayatun (Journal MISSY (Management and Business Strategy), 2024)
The aim of this research is to determine the influence of the Tapak Suci pencak silat extracurricular on improving the disciplinary character of students at SD Muhammadiyah Sugio Lamongan. This research uses a field research design with a quantitative type of research with a total sample of grades 4 and 5, totaling 65 students. Based on the research results, it can be concluded as follows: 1. Tapak Suci pencak silat extracurricular activities run regularly according to the specified schedule. 2. During the Tapak Suci pencak silat extracurricular process, all students looked very enthusiastic because they not only learned martial arts but also learned to control themselves so that indirectly the students' character and level of discipline increased. 3. Tapak Suci pencak silat extracurricular has had a significant positive impact on students' level of discipline.4. By regularly practicing Extracurricular Pencak Silat Tapak Suci, you can help students develop habits of hard work, responsibility and perseverance as well as good manners in achieving personal progress for students.